HUMAN RESOURCES EMPOWERMENT IN GLOBAL COMPETITION - Roy Sumaryono (STIE Mahardhika, 2022)
Increasing employee productivity is important role in achieving of company effectiveness. Job satisfaction is important because it will improve performance and have an effect on increasing employee and company productivity. This study uses quantitative methods and data analysis using path analysis. The population used is the truck mixer driver PT. Merak Jaya Beton Karang Pilang Plant Surabaya as many as 42 people and the respondents used were all mixer truck drivers. The results showed that workload had a significant effect on work productivity, the total effect value = 0.337 and self-leadership had no significant effect on work productivity, the total effect value = 0.279